Relationship between positive parenting and cyberbullying perpetration among adolescents: role of self-esteem and smartphone addiction - Kim, Ji Hye; Song, Hye Young; Jung, Gye Hyun (Frontiers in Psychology, 2024)
Introduction Adolescents may perpetrate cyberbullying in cyberspace, which they perceive as a medium of social communication, and cyberbullying perpetration is closely related to adolescent behavior, mental health, and development. This study aimed to examine the relationship of certain factors related to cyberbullying in adolescents using the framework of Jessor’s problem behavior theory. Methods This cross-sectional study investigated the mediating effect of adolescent self-esteem and smartphone addiction in the relationship between positive parenting and adolescent cyberbullying perpetration. The secondary analysis used data from the 2018 Korean Children and Youth Panel Survey. The data on positive parenting, adolescent self-esteem, smartphone addiction, and perpetration of cyberbullying of 2,394 Korean adolescents (boys: 1,297, 54.2%) were analyzed. Hayes’ PROCESS macro program was used to confirm the mediating role. Results The results revealed that 26.5% (n = 634) of adolescents had perpetrated cyberbullying. Positive parenting did not directly relate to cyberbullying perpetration. Adolescent self-esteem and smartphone addiction played a mediating role between positive parenting and adolescent cyberbullying. Discussion Individual adolescent characteristics and parent/family system characteristics should be considered in policies aimed at preventing adolescent cyberbullying perpetration, preceded by the management of appropriate smartphone use. Improving young people’s self-esteem and teaching them how to use smartphones correctly can help prevent cyberbullying.